2012
DOI: 10.1055/s-0032-1316582
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Use of Novel 3,3′-Disubstituted 2,2′-Bipyridine-Based Chiral Ligands: Asymmetric Catalysis in Direct Aldol Reactions

Abstract: A wide range of chiral ligands based on the 2,2′-bipyridine scaffold were designed and synthesized. In complexation with metal Lewis acids, the reactivity and stereoselectivity of the prepared chiral ligands were examined in asymmetric catalytic direct aldol reactions, thus providing the desired products with high stereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 1 publication
2
22
0
Order By: Relevance
“…N 3 , N 3′ ‐Bis[( S )‐pyrrolidin‐2‐ylmethyl]‐2,2′‐bipyridine‐3,3′‐diamine(2b): Compound 1b was prepared according to a reported procedure and the 1 H NMR spectroscopic data was consistent with the reported values 5i. Compound 1b : 1 H NMR (400 MHz, CDCl 3 ): δ = 13.02 (s, 2 H), 9.03–9.05 (t, 2 H), 8.38–8.39 (t, 2 H), 7.35 (dd, J = 8.4, 4.4 Hz, 2 H), 3.89 (dd, J = 9.6, 5.2 Hz, 2 H), 2.89–3.11 (m, 4 H), 2.17–2.23 (m, 2 H), 1.92–2.00 (m, 4 H), 1.67–1.73 (m, 4 H) ppm.…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…N 3 , N 3′ ‐Bis[( S )‐pyrrolidin‐2‐ylmethyl]‐2,2′‐bipyridine‐3,3′‐diamine(2b): Compound 1b was prepared according to a reported procedure and the 1 H NMR spectroscopic data was consistent with the reported values 5i. Compound 1b : 1 H NMR (400 MHz, CDCl 3 ): δ = 13.02 (s, 2 H), 9.03–9.05 (t, 2 H), 8.38–8.39 (t, 2 H), 7.35 (dd, J = 8.4, 4.4 Hz, 2 H), 3.89 (dd, J = 9.6, 5.2 Hz, 2 H), 2.89–3.11 (m, 4 H), 2.17–2.23 (m, 2 H), 1.92–2.00 (m, 4 H), 1.67–1.73 (m, 4 H) ppm.…”
Section: Methodsmentioning
confidence: 59%
“…( S )‐ tert ‐Butyl 2‐[(3′‐Amino‐2,2′‐bipyridin‐3‐yl)carbamoyl]pyrrolidine‐1‐carboxylate (4b): Compound 3b was prepared according to a previous procedure 5i. By following the same procedure as that of 4a , starting from 3b (186 mg, 1.0 mmol), 4b was prepared as a yellow foam (249 mg, 65 % yield).…”
Section: Methodsmentioning
confidence: 99%
“…As compared to that of chiral phosphine and amine catalysts, chiral bipyridine catalysts have attracted great attention owing to their highly efficient stereocontrol and unique coordination capabilities . Noticeably, a lot of reports indicated that the installation of an axially unfixed bipyridine in the designed organocatalysts may afford them favorable conformational properties responsible for efficient chiral induction, and therefore the effect of the steric hindrance originating from reactant or catalyst itself could be minimized . Meanwhile, our preliminary work further testified that the ligands of 2,2′‐bipyridine are easy to be modified and readily combined with functional groups compared with other ligands in current reported, similarly, such as L ‐proline and L ‐phenylalanine as chiral amino acids.…”
Section: Introductionmentioning
confidence: 67%
“…The UV‐Visible diffuse reflectance (Uv‐vis DR) spectra of all related samples are shown in Figure . Firstly, as can be seen in Figure A‐g, the absorption peaks for Z at 255 nm and 311 nm belonged to the transitional absorption of π → π* and n → π* in the bipyridyl structures, while ZnBMMs (Figure A‐b) exhibited a weak absorption peak of around 246 nm, which may be due to the nanoporous effect of BMMs ,. Although pure ZZnBMMs (Figure A‐a) possessed the similar peaks in the range of 250–400 nm, the occurrences of characteristic peaks red‐shifted from 255 to 267 nm, and 311 to 328 nm.…”
Section: Resultsmentioning
confidence: 91%
“…The bimodal mesoporous SiO 2 (BMMs) possess a high surface area (>700 m 2 /g), large pore volume (up to 3.5 cm 3 /g), modifiable surface and controllable bimodal mesopores with small ordered mesopores of around 3 nm and the large mesopores (15‐50 nm) of uniform intra‐nanoparticle . (2 S,2’S)‐N,N’‐([2,2’‐bipyridine]‐3,3’‐diyl) bis(pyrrolidine‐2‐carboxamide) (abbreviated as Z) was synthesized by our collaborator, which presents a good catalytic activity for asymmetric aldol reaction under homogeneous system ,. In our previous studies, a novel heterogeneous chiral catalyst (Z‐BMMs) was prepared via immobilization of Z onto the mesoporous channels of BMMs (Z‐BMMs) by hydrogen bond method, and showed a higher catalytic activity for asymmetric aldol reaction between cyclohexanone and 4‐nitrobenzaldehyde, as compared to that of homogenous catalysts .…”
Section: Introductionmentioning
confidence: 99%